The Role of Teacher Technology Experiences and School Technology Interactivity in Teachers' Culturally Responsive Teaching. Issue 2 (3rd April 2022) - Cheng, Ming-Min; Chuang, Hsueh-Hua; Smith, Thomas J.
Abstract: The present study examined how the type of school technology and teachers' technological experiences (either personal or pedagogical) were related to teacher perceptions of culturally responsive teaching in technology-supported learning environments. Additionally, the study assessed the moderating effects of school technology interactivity on the relationship between teacher technology experiences and their perception of culturally responsive teaching in these environments. Hierarchical linear modeling was conducted on data from 257 teachers in Taiwan. Results found that the presence of technology interactivity in schools, teachers' personal technology experiences, and technology experiences in teaching each had a positive and statistically significant effect on teachers' perception of culturally responsive teaching. In addition, results found that the presence of interactive technology had no significant moderating effect on the relationship between either personal technology integration or technology integration in teaching and any of the five dimensions of culturally responsive teaching. The results suggest that, in addition to technological infrastructure renovation, schools should provide teachers with professional development programs and support which encourages them to create a technology-infused environment to address the connections between students' cultural contexts and their learning contents.